SARS-CoV-2 in Transit: Characterization of SARS-CoV-2 Genomes From Venezuelan Migrants in Colombia. (September 2021) - Patiño, Luz H.; Ballesteros, Nathalia; Muñoz, Marina; Castañeda, Sergio; Hernández, Carolina; Gomez, Sergio; Florez, Carolina; Rico, Angelica; Pardo, Liseth; Hernandez-Pereira, Carlos E.; Delgado-Noguera, Lourdes; Grillet, Maria E.; et al.
Highlights: SARS-CoV-2 lineages were identified among Venezuelan migrants in Colombia. The spike L18F mutation was identified in genomes from Venezuelan migrants. Colombian and Venezuelan isolates from the northern border were genetically similar. Within Colombian departments, Venezuelan and Colombian isolates were distinct. This is the first report to describe the presence of B.1.1.255 lineage in Colombia. ABSTRACT: Objectives: To evaluate the genomic epidemiology of SARS-CoV-2 from Venezuelan migrants living in Colombia. Methods: This study sequenced SARS-CoV-2 from 30 clinical specimens collected from Venezuelan migrants. Genomes were compared with the Wuhan reference genome to identify polymorphisms, reconstruct phylogenetic relationships and perform comparative genomic analyses. Geographic, sociodemographic and clinical data were also studied across genotypes. Results: This study demonstrated the presence of six distinct SARS-CoV-2 lineages circulating among Venezuelan migrants, as well as a close relationship between SARS-CoV-2 genomic sequences obtained from individuals living in the Venezuelan-Colombian border regions of La Guajira (Colombia) and Zulia (Venezuela). Three clusters (C-1, C-2 and C-3) were well supported by phylogenomic inference, supporting the hypothesis of three potential transmission routes across the Colombian-Venezuelan border. These genomes included point mutations previously associated with increased infectivity. A mutation (L18F) in the N-terminal domain of the spike protein that has been associated with compromised binding of neutralizing antibodies was found in 2 of 30 (6.6%) genomes. A statistically significant association was identified with symptomatology for cluster C2. Conclusion: The close phylogenetic relationships between SARS-CoV-2 genomes from Venezuelan migrants and from people living at the Venezuela-Colombian border support the importance of human movements for the spread of COVID-19 and for emerging virus variants.